2013
DOI: 10.14568/cp2012005
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological diversity in the Unfinished Sacristy building of the Convent of Christ, Tomar, and evaluation of its biocide-based control

Abstract: Deterioração da pedra Alteração biológica Bactérias Fungos Biocidas Resumo Com o objetivo de caracterizar os microrganismos que colonizam as paredes calcárias da Sacristia Incompleta do Convento de Cristo, em Tomar, e estudar em laboratório o seu controlo por agentes biocidas, recolheram-se por swabbing amostras de seis locais e caracterizou-se a flora microbiana presente cultivável em laboratório, recorrendo a técnicas de microbiologia clássica. Verificou-se a presença de fungos, de bactérias heterotróficas e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Moreover, Sanmartín and Carballeira [4], while working to evaluate the effects of similar biocidal treatments in heterotrophic microbial communities in the Monastery of San Martiño Pinario (Santiago de Compostela, Spain), also verified that Biotin T was the most effective treatment against fungal species. Additionally, Mateus et al [17] also observed a good Biotin T efficiency against fungi retrieved from limestone walls of the unfinished Sacristy of the Convent of Christ (Tomar, Portugal). Nonetheless, it is also noteworthy to mention that while working on churches in Segovia (Spain), de los Ríos et al [18] noticed that Biotin T application resulted in a cleaner stone surface, although unfortunately fungal hyphae were detected after two months of treatment application.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, Sanmartín and Carballeira [4], while working to evaluate the effects of similar biocidal treatments in heterotrophic microbial communities in the Monastery of San Martiño Pinario (Santiago de Compostela, Spain), also verified that Biotin T was the most effective treatment against fungal species. Additionally, Mateus et al [17] also observed a good Biotin T efficiency against fungi retrieved from limestone walls of the unfinished Sacristy of the Convent of Christ (Tomar, Portugal). Nonetheless, it is also noteworthy to mention that while working on churches in Segovia (Spain), de los Ríos et al [18] noticed that Biotin T application resulted in a cleaner stone surface, although unfortunately fungal hyphae were detected after two months of treatment application.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, quaternary ammonium compounds, phenols, aldehydes, and alcohols are a clear example of disinfectants, with temporary results and long-term damage to the preserved artifacts [2,7,8]. Environmental awareness, side effects of disinfectants and inhibitors led to the need for new materials with biocidal effects.…”
Section: Introductionmentioning
confidence: 99%